True polar wander and long-wavelength dynamic topography - Spada, Giorgio (Tectonophysics, 1993)
Spada, G., 1993. True polar wander and long-wavelength dynamic topography. In: M.J.R. Wortel, U. Hansen and R. Sabadini (Editors), Relationships between Mantle Processes and Geological Processes at or near the Earth's Surface. Tectonophysics, 223: 3–13. We analyze the potential influence of True Polar Wander, the global motion of the Earth's mantle with respect to the rotation axis, on the long-wavelength pattern of the Earth's dynamic topography. Internal mass redistributions, related to mantle convection, subduction episodes and thermal processes associated to plate formation, produce two main effects. First, they induce both a geoidal and topographic signal at the Earth's surface. Second, they change the Earth's inertia tensor. As a consequence, the Earth's rotation axis may be subject to excursions with respect to the whole mantle. Since the integrated effect of the internal heterogeneities defines the equator of the Earth, the present-day pattern of both long-wavelength geoid and dynamic topography are therefore expected to be affected to some extent by True Polar Wander (TPW). Our results suggest that the observed presence of maxima and minima for the non-hydrostatic geoid and dynamic topography in the equatorial region is due to a global readjustment of the Earth's shape caused by True Polar Wander.